Building an mandiri village of herbal medicine in an effort to improve the health of the Taula'a village Gorontalo District - Hamsidar Hasan; Madania Madania (Univeristas Negeri Gorontalo, 2022)
Herbal medicine is a medicine made from natural ingredients, either plants, animals, or minerals. Herbal medicines are widely used by the people of Indonesia to treat certain symptoms or diseases. Although this medicine is made from natural ingredients and has been used for a long time, it is necessary to know how to take safe herbal medicines to avoid side effects. This service aims to build the independence of the Taula'a Village community in terms of treatment using herbal medicines. Independent in terms of sources of herbal medicines, independent in terms of management, and independent in terms of their use. The methods used are lectures, education, and direct practice on how to cultivate medicinal plants in the yard, how to cultivate, and how to use herbal medicines. Evaluation of the success of community service based on increasing knowledge after education and being able to process herbal medicines with raw materials based on spices to improve health.